Silk fibroin film from golden‐yellow Bombyx mori is a biocomposite that contains lutein and promotes axonal growth of primary neurons. Issue 5 (May 2016) - Pistone, Assunta; Sagnella, Anna; Chieco, Camilla; Bertazza, Gianpaolo; Varchi, Greta; Formaggio, Francesco; Posati, Tamara; Saracino, Emanuela; Caprini, Marco; Bonetti, Simone; Toffanin, Stefano; Di Virgilio, Nicola; et al.
ABSTRACT: The use of doped silk fibroin (SF) films and substrates from Bombyx mori cocoons for green nanotechnology and biomedical applications has been recently highlighted. Cocoons from coloured strains of B. mori, such as Golden‐Yellow, contain high levels of pigments that could have a huge potential for the fabrication of SF based biomaterials targeted to photonics, optoelectronics and neuroregenerative medicine. However, the features of extracted and regenerated SF from cocoons of B. mori Golden‐Yellow strain have never been reported. Here we provide a chemophysical characterization of regenerated silk fibroin (RSF) fibers, solution, and films obtained from cocoons of a Golden‐Yellow strain of B. mori, by SEM, 1 H‐NMR, HPLC, FT‐IR, Raman and UV‐Vis spectroscopy. We found that the extracted solution and films from B. mori Golden‐Yellow fibroin displayed typical Raman spectroscopic and optical features of carotenoids. HPLC‐analyses revealed that lutein was the carotenoid contained in the fiber and RSF biopolymer from yellow cocoons. Notably, primary neurons cultured on yellow SF displayed a threefold higher neurite length than those grown of white SF films. The results we report pave the way to expand the potential use of yellow SF in the field of neuroregenerative medicine and provide green chemistry approaches in biomedicine. © 2016 Wiley Periodicals, Inc. Biopolymers 105: 287–299, 2016.